2021
DOI: 10.3389/fendo.2021.703167
|View full text |Cite
|
Sign up to set email alerts
|

The miR-4739/DLX3 Axis Modulates Bone Marrow-Derived Mesenchymal Stem Cell (BMSC) Osteogenesis Affecting Osteoporosis Progression

Abstract: Osteoporosis is a complex multifactorial disorder linked to various risk factors and medical conditions. Bone marrow-derived mesenchymal stem cell (BMSC) dysfunction potentially plays a critical role in osteoporosis pathogenesis. Herein, the study identified that miR-4739 was upregulated in BMSC cultures harvested from osteoporotic subjects. BMSCs were isolated from normal and osteoporotic bone marrow tissues and identified for their osteogenic differentiation potential. In osteoporotic BMSCs, miR-4739 overexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…miRNA could bind to the 3 ′ UTR region of related genes to suppress its translation and then affect numerous biological processes [10,19]. Studies have confirmed that miRNAs are essential in BMSC osteogenic differentiation [20,21]. For example, in osteogenic differentiation, RUNX2 is a targeted regulatory gene of miR-135 [22].…”
Section: Discussionmentioning
confidence: 99%
“…miRNA could bind to the 3 ′ UTR region of related genes to suppress its translation and then affect numerous biological processes [10,19]. Studies have confirmed that miRNAs are essential in BMSC osteogenic differentiation [20,21]. For example, in osteogenic differentiation, RUNX2 is a targeted regulatory gene of miR-135 [22].…”
Section: Discussionmentioning
confidence: 99%
“…53 While the sparse study has paid attention to using a D-ECM to modulate the hypertrophic differentiation of BMSCs, which is the main cell source for articular defect repairing as the multipotential cells migrate from the bone marrow cavity into the defect area. [54][55][56] It has been known that the CCL is a transition zone connecting the cartilage and bone parts, mainly containing hypertrophic chondrocytes that transform from chondrocytes and then are calcified to form osteoblasts. 57,58 It is suggested that the D-ECMs derived from osteoblasts, Cho, and HCho should all have a large or small effect on BMSC hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…OB originate from BMSCs and are closely related to new bone formation, which are mainly responsible for the synthesis and secretion of bone matrix and the mineralization of bone matrix, thus playing a vital role in bone formation ( Li et al, 2021 ). POT is produced by OB in the bone marrow and acts as a paracrine–autocrine regulator of bone formation ( Elabd et al, 2008 ; Ein-Dor et al, 2018 ).…”
Section: Pot and Cells Regulating Bone Metabolismmentioning
confidence: 99%